Pengaruh Health Education Perilaku Hidup Bersih dan Sehat (PHBS) Menggunakan Metode Audio Visual dan Demonstrasi Terhadap Keterampilan Melakukan Perilaku Hidup Bersih dan Sehat : Pada Siswa Sekolah Dasar Negeri 5 Besuki - Salimatul Amalia; Nur Hamim; Rizka Yunita (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Clean and Healthy Living behavior in schools is a set of behaviors that are practiced in the school environment, so that it is independently able to prevent disease, improve health, and play an active role in creating a healthy environment . Health education is clean and healthy living behavior using audio-visual and demonstration methods. This study aims to determine the effect of health education using audio visual and demonstration methods on the skills of clean and healthy behavior in elementary school students 5 besuki. This research method uses quasi experimental approach with two-group pre test and post test design. The population of all students aged 6-12 SDN 5 besuki as many as 95 students SDN 5 besuki, sampling techniques used purposive sampling with a sample of 77 respondents. The instruments used are PHBS, SOP, and module videos. The Data obtained from the study were analyzed using the Wilcoxon Test and mann whitney Test. The results showed that the health education group using audio visual pre-test method amounted to 88.5 post-test 30.8 in the health education group using pre-test demonstration method amounted to 89.6 post-test 31.2. Wilcoxon test results in obtaining a p-value of 0.000 in the audio-visual and demonstration groups. Mann-whitneyy test results in getting the difference score from the difference between the two groups in getting the value of p-value 0.129 with an average value in the Audio-visual group of 35.42 and 42.49 demonstration group. It is expected that respondents who have not behaved in a clean and healthy life can apply health education using effective demonstration methods because the demonstration method is practiced directly by researchers and respondents so that it can be done independently.